Impact of Various Types of Fibres on the Mechanical Properties of Lightweight Concrete - Karem Saja T.Abd Al; Al-Asadi Ali K. (Civil and Environmental Engineering)
Impact of various types of fibres on the Mechanical propertes of Lightweght Concrete. This research aims to study the effect of adding fibers on the fresh, and hard propertes of light concrete. To achieving this goal, 13 mixtures were examined, containing different types and proportions of fiber, where the precipitation was examined, as well as the compressive strength, the splitting strength, the fracture modulus, in addition to the workability . The basic variables for this research. The type of fibre, where four types of fibre (steel hooked end, crimped steel, glass, and polypropylene,) were used, and the second variable is the percentage of fibre, as the ratios were as follows (0.3, 0.5, 0.6, 0.8, 1, and 1.3 ), As for the third variable, it was to combine the types of fibers with each other to obtain the hybrid fibre and study its effect on lightweghit concrete. The results showed that the mixing of steel fiber by 0.5 with the class by 0.5% with 0.3 polypropylene led to decrease the workability of mix, on other hand, Compressive strength and splitting tensile strength, in addition to other properties of concrete were improved, where the percentage of increase in the compressive and splitting strength was 52.17 and 45.36 %, respectively. Furthermore, the hooked end steel showed a better performance than crimped steel in improving proprieties of lightweight concrete.